Approaching Spiritual and Existential Care Needs in Health Education: Applying SOPHIE (Self-Exploration through Ontological, Phenomenological, and Humanistic, Ideological, and Existential Expressions), as Practice Methodology - Ali, Gulnar (Religions, 2020)
Addressing existential and spiritual care needs, often remains a challenge in health education. Spirituality is a subjective human experience that shapes how individuals make meaning, construct knowledge, develop their own sense of reality, and bring personal and social transformation. To inspire health and social students at a London based University; learners were engaged into philosophical reasonings associated with the meaning to care. SOPHIE (Self-exploration through Ontological, Phenomenological and Humanistic, Ideological, and Existential expressions)—a reflective practice tool was applied during in-class activities from June 2019-2020. Using SOPHIE as a tool, students were encouraged to explore existential and ontological care aspects by engaging into transformative learning approaches. Participants identified their own existential and spiritual care needs by reflecting on their own meaning making process. SOPHIE enabled resilience and authenticity among learners as a reflexive discourse.